Pengaruh Keselamatan Kerja dan Kesehatan Kerja terhadap Kinerja Pegawai UPTD Wilayah Pelayanan X - Najmi Nur Ihsan; Dian Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of occupational safety and health on employee performance in Service Area X Technical Implementation Unit (UPTD). The research method used was quantitative with a descriptive and associative approach. The study population was field employees of Service Area X Technical Implementation Unit (UPTD), with a sample of 66 respondents. Data collection was conducted through questionnaires, interviews, and documentation. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination using SPSS version 26. The results showed that occupational safety was in the good category with an average score of 3.80, occupational health was in the good category with an average score of 3.63, and employee performance was in the good category with an average score of 3.65. Partially, occupational safety had a positive and significant effect on employee performance with a calculated t-value of 3.846 and a significance level of 0.000, while occupational health had a positive and significant effect on employee performance with a calculated t-value of 3.525 and a significance level of 0.001. Simultaneously, occupational safety and health have a positive and significant effect on employee performance, with a calculated F-value of 25.389 and a significance level of 0.000. The coefficient of determination of 44.6% indicates that employee performance is influenced by occupational safety and health, while 55.4% is influenced by other factors not examined. The conclusion of this study is that occupational safety and health have a positive and significant effect on employee performance in Service Area X UPTD. Therefore, increasing the implementation of occupational safety and health programs can support improved employee performance. Keywords: Occupational Health, Occupational Safety, Employee Performance, Human Resource Management